2012
DOI: 10.1016/j.mmcr.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological efficacy of micafungin on Geosmithia argillacea infection in a cystic fibrosis patient

Abstract: Cystic fibrosis (CF) patients are at high risk of colonization of the airways by a number of fungi, including the emerging opportunistic fungus Geosmithia argillacea. We report the eradication of respiratory G. argillacea associated with clinical resolution of severe symptoms by high-dose and prolonged micafungin therapy in a young CF patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…infections. Notably, in the French reported case, although caspofungin treatment resulted in improvement in the clinical status of the patient, eradication was obtained only with high‐dose and prolonged micafungin therapy . Furthermore, in our in vitro combination testing we did not observe any synergy for itraconazole‐micafungin and terbinafine‐micafungin combinations.…”
Section: Discussionmentioning
confidence: 48%
“…infections. Notably, in the French reported case, although caspofungin treatment resulted in improvement in the clinical status of the patient, eradication was obtained only with high‐dose and prolonged micafungin therapy . Furthermore, in our in vitro combination testing we did not observe any synergy for itraconazole‐micafungin and terbinafine‐micafungin combinations.…”
Section: Discussionmentioning
confidence: 48%
“…In contrast, it seems more limited in CF, with a unique case of respiratory infections caused by this species complex having been reported for this genetically inherited disease (14). Nevertheless, the present identification of some genotypes chronically colonizing the lower airways of patients with CF demonstrates the persisPatient P17 -sampling date 1 9 9 6 1 9 9 7 / 0 9 / 2 5 2 0 0 1 1 9 9 8 / 0 1 / 2 1 1 9 9 7 / 1 2 / 1 1 1 9 9 7 / 1 0 / 2 7 tence of these usually saprophytic fungi in the respiratory tract and their multiplication, suggesting their contribution to the inflammatory reaction which progressively leads to clinical and functional deterioration, as demonstrated for long-term colonization of the airways by Aspergillus fumigatus or Candida albicans (32,33,34).…”
Section: Discussionmentioning
confidence: 98%
“…In CF patients, all species of the R. argillacea complex except R. eburnea have been reported to colonize the airways (8). While no clear relationship was established in the CF context between the colonization of the airways by these fungi and a clinical or functional deterioration, the recent report of R. argillacea pathogenicity in one patient with CF prompts further investigation (14). In addition, differences between these closely related species in their antifungal susceptibility profiles further emphasize the need for an accurate identification of the fungus for optimal therapy (1,8).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In total, four studies from France and the United Kingdom have reported the colonization of 18 CF patients by the R. argillacea species complex 8,9,19,20. However, the presence or persistence of these fungi was associated with a decrease in lung function or with pulmonary exacerbation in only one case 20. Our knowledge about the relevance and role of this fungus in CF is still limited because this pathogen has been only recently described, and data about its real prevalence in the CF population are lacking.…”
Section: Discussionmentioning
confidence: 99%